NEDD4-family E3 ligase dysfunction due to PKHD1/Pkhd1 defects suggests a mechanistic model for ARPKD pathobiology - Jun-ya Kaimori (Nature Portfolio, 2017)
Abstract Autosomal recessive polycystic kidney disease (ARPKD) is an important childhood nephropathy, occurring 1 in 20,000 live births. The major clinical phenotypes are expressed in the kidney with dilatation of the collecting ducts, systemic hypertension, and progressive renal insufficiency, and in the liver with biliary dysgenesis, portal tract fibrosis, and portal hypertension. The systemic hypertension has been attributed to enhanced distal sodium reabsorption in the kidney, the structural defects have been ascribed to altered cellular morphology, and fibrosis to increased TGF-β signaling in the kidney and biliary tract, respectively. The pathogenic mechanisms underlying these abnormalities have not been determined. In the current report, we find that disrupting PKHD1 results in altered sub-cellular localization and function of the C2-WWW-HECT domain E3 family of ligases regulating these processes. We also demonstrate altered activity of RhoA and increased TGF-β signaling and ENaC activity. Linking these phenomena, we found that vesicles containing the PKHD1/Pkhd1 gene product, FPC, also contain the NEDD4 ubiquitin ligase interacting protein, NDFIP2, which interacts with multiple members of the C2-WWW-HECT domain E3 family of ligases. Our results provide a mechanistic explanation for both the cellular effects and in vivo phenotypic abnormalities in mice and humans that result from Pkhd1/PKHD1 mutation.